PERSEPSI MASYARAKAT KOTA PEKANBARU TENTANG APLIKASI PINJAMAN ONLINE - Susi Susanti; Jonyanis " (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2020)
The background of this research is due to the increase in the number of online loans in the city of Pekanbaru which causes various phenomena including the emergence of various illegal online loan applications that are problematic, hacking of personal data by violating the personal access rights of consumers, and the amount of disturbing terror committed by money collectors to borrowers with way that is not fair, but these various problems still make some people still make loans online in various applications. The purpose of this study was to determine the perception of the people of Pekanbaru about online loans and what are the reasons people make loans online. This research was conducted in Tampan District, Pekanbaru. The population in this study are all people who make loans online in the city of Pekanbaru in 2019 with 480,262 borrowers. So that the sample was drawn using simple random sampling and obtained a total of 100 people. The results showed that the majority of respondents had good perceptions (70.0%), poor perspectives (27.0%), not good (2.0%) and very good (1.0%) of online loan applications. Based on the age of 21-30 years have the most unfavorable perceptions. Women have the most unfavorable perceptions and no women have very good perceptions about online loans. married respondents have the highest level of unfavorable perceptions. Respondents with income equal to Rp. 2,557,000 has the highest level of unfavorable perceptions, there are respondents who have income less than Rp. 2,557,000 have a bad perception level, and there is one respondent who has a large income of Rp. 2,557,000 has a very good perception level . The majority of the reasons respondents make loans online are the ease of collateral / absence of collateral, this is because 74% of respondents choose the convenience of collateral as a reason for lending online. The reason that at least done by respondents is recommendations from families. Keywords: Perception, Online Loans